Pengaruh Kompetensi, Budaya Organisasi, Soft Skill dan Pengembangan Karir Terhadap Kinerja Pegawai di PT. Bank Sumut Pusat Medan - Wardani , Nila Ayu; Ritonga , Ilham Muharaq; Putra , Rizky (Jurnal Ekonomi Bisnis Digital, 2022)
This study aims to analyse the significant influence of competence, organisational culture, soft skills and career development on employee performance of PT. Central Sumatera Bank Medan. The total population in this study amounted to 531 employee and use 84 employee as a sample. The analysis technique used is multiple regression analysis. The results showed that competence, organisational culture, soft skills and career development had a significant effect on employee performance at PT. Central Sumatera Bank Medan. As simultan effect the competence, organizational culture, soft skill and career development had a significant effect on employee performance at PT. Central Sumatera Bank.